30 Learning from engagement with and Use of the ambitions for palliative and end of life care national framework. (30th January 2023) - Borgstrom, Erica; Henry, Claire; Jordan, Joanne; St-Ledger, Una
Abstract : Introduction: The Ambitions for Palliative and End of Life Care: a national framework for local action (2015) was relaunched in 2021 for another five years. The Framework focuses on six ambitions, underpinned by eight guidance for action foundations. Previously, we surveyed for service examples to map use of the Framework. Most responses were from specialist providers; Ambition 6 (all communities are prepared to care) received fewest responses. Aims: To further investigate understanding of the Framework, and how it has been used in practice across sectors. Methods: We undertook 17 individual online interviews (identified as case studies from the survey data) and four online focus groups. Focus groups were based on professional role or interest (e.g. commissioners, public, service managers, healthcare staff) and contained between 2–8 participants. Questions sought to fill gaps in and extend the survey data. All data was transcribed and coded thematically. Results: We identified four main themes about how people use, think about, and develop their work using the Ambitions: (1) strategy and self-assessment, (2) partnership working, (3) sharing learning, (4) community. Community was widely understood as difficult to conceptualise. Across themes, people listed facilitators, challenges, and concerns about inequitable access due to challenges and who is considered 'community'. Facilitators comprised provision of a common set of values and shared language. Challenges included poor understanding of the Framework beyond palliative and end of life care (PEOLC) settings, difficulties in measuring progress, and lack of funding. Conclusions: The Ambitions Framework is better understood and applied by those working within adult PEOLC, with integrated care and resourcing remaining as challenges. The next phase is a series of participatory workshops with stakeholders to seek solutions to these issues. Impact: The ongoing findings and project promote engagement with the Framework, shared learning, and be used to develop strategies to progress the Ambitions. Reference(s): 1. Borgstrom, E., Jordan, J., and Henry C. (2022) Ambitions for Palliative and End of Life Care: Mapping Examples of Use in Practice. Milton Keynes: The Open University